Estimating in geometric 3D CAD - Olatunji, Oluwole; Sher, W. (Emerald Group Publishing Ltd., 2015)
© Emerald Group Publishing Limited. Purpose – The purpose of this paper is to elicit the activities in geometric 3D computer-aided design (CAD) estimating. Construction estimators usually target the structural integrity of data underlying project designs while measuring quantities and developing estimates. However, there are different ways to this. There is considerable evidence to suggest substantial distinction between data structuring in geometric and parametric CAD (building information modelling). Each of these platforms also appeals to estimators in the various practice domains differently. Regardless, the developments in the use of geometric and parametric CAD for design and management purposes have been rapid. Design/methodology/approach – The study focuses on the various perspectives within the different construction business domains. Interviews, focus group discussions and direct observation methods were used to explore data on estimating activities in 3D CAD from two public organizations, two large contracting firms, two quantity surveying consulting practices, two specialist-project companies and four software development and vending firms. These involved 17 middle-top management estimators who have had extensive experience in the industry. As the activities were elicited, participants were able to ascribe relative importance to each of the activities, and these were logically compared across the different practice domains. Findings – Thirty-one activities were identified as the components of estimators’ procedures leading to reliable outcomes in estimating 3D CAD designs. Logical correlations were discussed through extant literature towards forming a centroid model which could be used for numerous industry applications, including software development, knowledge transfer between organizations, employees’ hands-on training, curriculum design for academic institutions and as a policy framework for professional institutions on estimating practice. Further areas of research were also highlighted. Originality/value – This work is an original piece. It is neither published nor under consideration elsewhere.